Evaluating a young-onset dementia service from two sides of the coin: staff and service user perspectives - Clarissa Giebel; Cassie Eastham; Jacqueline Cannon; John Wilson; Janet Wilson; Anna Pearson (BMC, 2020)
Abstract Background People with young-onset dementia (YOD) can often struggle getting the right treatment. This is because of their frequently different characteristics and needs compared to people with late-onset dementia. The aim of this project was to assess a memory service for its adaptation to the needs and wishes of people with YOD and their carers. Methods This project evaluated a memory service in the North West of England by performing two focus groups with clinical staff and six semi-structured interviews with people with YOD and carers. The focus groups took place on site and lasted one hour each. People with YOD and their carers were identified via the memory clinics caseload and via the local Alzheimer's Society charity organisation. Both focus groups and interviews were audio-recorded and transcribed, and data were analysed using thematic analysis. The public (a person living with YOD and his carer) were involved from the design stages of the project through to the analysis and dissemination. Results Eleven members of staff with different clinical backgrounds participated in the focus groups and six interviews were held with people with YOD and their carers. Both indicated that whilst the diagnostic process is relatively well conducted at the service, the post-diagnostic service has many gaps. These include limited post-diagnostic support by the service, better enabling peer support, as well as providing meaningful activities, as some activities provided might be more suitable to older adults with dementia. Conclusions Post-diagnostic services and support for people with YOD and their carers need to be improved. The next step will be to implement the findings from this service evaluation in practice and improve service satisfaction and relevance to people with YOD.